Parametric analysis of PCM thermal storage system in an annual period - Osterman, Eneja (Strojniški vestnik, 2018)
Using thermal energy storage (TES) in phase change materials (PCMs) can reduce energy consumption in buildings. In summer, cold can be stored at night and released during the daytime therefore reducing the temperature while in winter, the system can be connected to a solar air collector that supplies heat. This article presents a paraffin based thermal storage unit and its annual operation. A 2D model is set up in Fluent, thereby calculating the thermal response of the unit. The cooling and heating modes along with a numerical analysis of different parameters are considered and the best ones are determined for the city of Ljubljana.
Keywords: fazno spremenljive snovi; latentni hranilnik toplote; letno delovanje; naravno hlajenje in ogrevanje; parametrična analiza